Gustavo Garza. El proceso de industrialización en la ciudad de México, 1821-1970. México : El Colegio de México, 1985. 446 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1986)
GUSTAVO GARZA. El proceso de industrialización en la ciudad de México (1821-1970). El Colegio de México, México, 1985.